Perlindungan Hukum Terhadap Pelapor Dugaan Tindak Pidana Narkotika Menurut Undang-Undang Nomor 35 Tahun 2009 dan Hukum Islam - Soleha, Anisatul; Rohmah, Siti Ngainnur (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The high number of narcotics abuse in Indonesia cannot be denied because of the minimum assistance or report from the community related to the presence of narcotics crime existing around them. In the perspective of Islamic Law, narcotics is like khamr in which if it is consumed then it will cause mind lost. Therefore, khamr is forbidden in Islam. This paper provides an understanding of legal protection towards the informant of narcotics crime allegation according to The Law Number 35 Year 2009 and to find out the legal protection towards the informant of narcotics crime allegation according to Islamic law. The author employed library research type with normative juridical approach. The research results showed that The Law Number 35 Year 2009 about narcotics gives legal protection towards the informant of narcotics crime allegation systematically. Started from the protection aspect towards the physique, protection towards the psychic, and legal assistance during the process of justice and right reinforcement, and obtain an award. Islamic law gives legal protection to the informant of khamr drinker. Islamic law gives the opportunity by giving the protection towards the informant of khamr drinker not to be punished and the khamr drinker must be punished to implement the punishment and had in line with Islamic teaching namely the execution of whiplash for 40 times.Keywords: Informant Legal Protection, Narcotics, Islamic Law. AbstrakTingginya angka penyalahgunaan narkotika di Indonesia tidak bisa di pungkiri, karena minimnya bantuan atau laporan dari masyarakat terkait adanya tindak pidana narkotika yang ada di sekitar mereka. Dalam perspektif hukum Islam, narkotika diqiyaskan dengan khamr, yang apabila diminum akan mengakibatkan hilangnya akal. Oleh karena itu khamr diharamkan dalam Islam. Tulisan ini memberikan pemahaman mengenai perlindungan hukum terhadap pelapor dugaan tindak pidana narkotika menurut Undang-Undang nomor 35 tahun 2009 dan perlindungan hukum terhadap pelapor dugaan tindak pidana narkotika menurut hukum Islam. Hasil penelitian menunjukkan Undang-Undang Nomor 35 tahun 2009 tentang narkotika memberikan perlindungan hukum terhadap pelapor dugaan tindak pidana narkotika secara sistematik. Mulai dari aspek Perlindungan terhadap fisik, perlindungan terhadap psikis, dan pendampingan hukum selama proses penegakkan hak dan keadilan, serta mendapatkan penghargaan. Hukum Islam memberikan perlindungan hukum terhadap pelapor peminum khamr. Hukum Islam memberikan kesempatan dengan memberikan perlindungan terhadap pelapor peminum khamr agar tidak dihukum dan wajib bagi seorang peminum khamr untuk melaksanakan hukuman atau had sesuai ajaran Islam, yaitu dengan terlaksananya dera sebanyak 40 kali.Kata Kunci: Perlindungan Hukum Pelapor, Narkotika, Hukum Islam